2022
DOI: 10.30813/bmj.v18i1.2829
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Sepeda Motor TVS

Abstract: This study aims to determine the effect of brand image and product quality individually and jointly on TVS motorcycle purchase decisions for Pamulang University students. The research method uses quantitative methods and uses primary and secondary data types. The population of this research is all Pamulang University students in 2019 by using purposive sumpling technique using the ancient rao formula in determining the number of samples as many as 100 respondents. The data analysis method used validity test, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…This result is also supported by the results of the analysis of respondents' answers, especially on the reputation indicator with the statement "Mie Sedaap always releases new products and innovations so I want to always try them". It is the same with research (Arifin & Setyaningrum, 2022) entitled "Analysis of the Influence of Halal Labeling, Price, Promotion, Taste, and Brand Image on the Purchase Decision of Kanzler Sausages by Millennials (Studies on Indomaret Sragen Supermarket Consumers)", furthermore "The Influence of Advertising Electronic Media, Brand Ambassador, and Brand Image on Purchase Intention (Case Study of Lemonilo Noodle Consumers in Surakarta City)" (Gunawati, 2022), on the results (Waluyo et al, 2023) entitled "The Effect of Product Variants and Brand Image on Decisions Purchasing Pucuk Harum Tea in Langsa City" and the last one entitled "The Effect of Brand Image and Product Quality on Purchase Decisions for TVS Motorcycles" (Pasaribu, 2022) researchers found that brand image variables had a positive and significant effect in this study. Shared or partial brand image has a significant and positive influence on consumer choice.…”
Section: The Effect Of Brand Image On Purchasing Decisionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is also supported by the results of the analysis of respondents' answers, especially on the reputation indicator with the statement "Mie Sedaap always releases new products and innovations so I want to always try them". It is the same with research (Arifin & Setyaningrum, 2022) entitled "Analysis of the Influence of Halal Labeling, Price, Promotion, Taste, and Brand Image on the Purchase Decision of Kanzler Sausages by Millennials (Studies on Indomaret Sragen Supermarket Consumers)", furthermore "The Influence of Advertising Electronic Media, Brand Ambassador, and Brand Image on Purchase Intention (Case Study of Lemonilo Noodle Consumers in Surakarta City)" (Gunawati, 2022), on the results (Waluyo et al, 2023) entitled "The Effect of Product Variants and Brand Image on Decisions Purchasing Pucuk Harum Tea in Langsa City" and the last one entitled "The Effect of Brand Image and Product Quality on Purchase Decisions for TVS Motorcycles" (Pasaribu, 2022) researchers found that brand image variables had a positive and significant effect in this study. Shared or partial brand image has a significant and positive influence on consumer choice.…”
Section: The Effect Of Brand Image On Purchasing Decisionsmentioning
confidence: 99%
“…To leave a good first impression on customers, businesses must address the three elements of a brand image. Consumer perceptions of a company's brand influence their final purchase decision (Pasaribu, 2022). Brand reputation can be evaluated in several ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seperti yang telah dikemukakan oleh (Pasaribu, 2021), terdapat beberapa indikator yang terdapat dalam brand image:…”
Section: Indikator Brand Imageunclassified
“…R. Saleh Syarif Bastaman No. 15 Empang, Bogor, Indonesia. BMR tour and travel agent, one of the companies that provide travel services and exciting vacation experiences to customers who want to use their services [3].…”
Section: Introductionmentioning
confidence: 99%